2021
DOI: 10.1002/art.41696
|View full text |Cite
|
Sign up to set email alerts
|

Protective Role of Collectin 11 in a Mouse Model of Rheumatoid Arthritis

Abstract: Objective. Collectin 11 (CL-11) is a soluble C-type lectin, a mediator of innate immunity. Its role in autoimmune disorders is unknown. We undertook this study to determine the role of CL-11 in a mouse model of rheumatoid arthritis (RA).Methods. A murine collagen-induced arthritis (CIA) model was used and combined two approaches, including gene deletion of Colec11 and treatment with recombinant . Joint inflammation and tissue destruction, circulating levels of inflammatory cytokines, and adaptive immune respon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…VEC1 expressed high levels of protective genes, such as COLEC11 (antiautoimmune response), 16 PLA2G2A (antimicrobe), 17 and CTHRC1 (repair after VEC injury), 18 and it was thus annotated as protective VECs (Figure 3C; Figure S11B). VEC1 also highly expressed HLA (human leukocyte antigen) genes like HLA-DPA1, HLA-DRB1 , and HLA-DRA (Figure 3C), which might mediate antigen processing and presentation of exogenous peptide antigens via the major histocompatibility complex class (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…VEC1 expressed high levels of protective genes, such as COLEC11 (antiautoimmune response), 16 PLA2G2A (antimicrobe), 17 and CTHRC1 (repair after VEC injury), 18 and it was thus annotated as protective VECs (Figure 3C; Figure S11B). VEC1 also highly expressed HLA (human leukocyte antigen) genes like HLA-DPA1, HLA-DRB1 , and HLA-DRA (Figure 3C), which might mediate antigen processing and presentation of exogenous peptide antigens via the major histocompatibility complex class (Figure 3D).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, another study reported that serum LRG1 levels were reduced after treatment with the anti-IL-6 receptor antibody tocilizumab [24]. T cells can differentiate into T helper 17 cells (Th17) or regulatory T cells (Tregs) under different stimulations [25]. The level of Th17 cells is positively associated with the disease activity of RA [26].…”
Section: Discussionmentioning
confidence: 99%
“…Unpaired t -test was employed for the comparison between two groups with unmatched data. Multiple comparison test, either One-way or Two-way, was used to compare the means of >2 independent groups [ 29 ]. p < 0.05 indicated a statistical significance level.…”
Section: Methodsmentioning
confidence: 99%